Dry microwave heating enables scalable fabrication of pristine holey graphene nanoplatelets and their catalysis in reductive hydrogen atom transfer reactions. (November 2018) - Savaram, Keerthi; Li, Mengjun; Tajima, Kentaro; Takai, Kazuyuki; Hayashi, Takuya; Hall, Gene; Garfunkel, Eric; Osipov, Vladimir; He, Huixin
Abstract: Current approaches for scalable production of holey graphene materials require graphene oxide or reduced graphene oxide as starting materials. The molecular basis fundamentally determines that the holey graphene materials thus generated still contain a large number of defects on their basal planes. The existence of these defects not only complicates fundamental studies but also influences practical applications due to the significance decrease in their conductivity and chemical stability. This work exploits microwave chemistry to enable rapid mass production of holey graphene nanoplatelets with their basal plane nearly intact. Interestingly, the unique chemistry also begets the generated nanoholes with edges rich in zigzag geometry. The near-pristine nature of the basal planes and the zigzag edges were clearly observed via atomic resolution TEM and further supported by the localized π-edge states studied via electron paramagnetic resonance (EPR) measurements. The holey graphene nanoplatelets were explored as metal free catalysts for hydrogen atom transfer reactions. These unique holey graphene nanoplatelets exhibited excellent catalytic activity, desired selectivity, and chemical stability for recyclability, which were not achievable by their counterpart holey graphene derivatives with basal plane defects. Graphical abstract: Image 1